Colloidal stability of native and cross-linked casein micelles and their potential use as nanocarrier for cyanidin-3-O-glucoside - Casanova, Federico (2017)
Casein micelles (CMs) are natural supramolecular assemblies present in milk. Their average hydrodynamic diameter is about 200nm and they present a hydrophobic core and a hydrophilic shell. CMscan be used as natural nanocarriers to deliver various moleculesof interest. Although CMs are quite stable against heat, their structure is highly sensitive to ionic changes, especially at acid pH. An interesting method to stabilize casein structure consists on itscross-linking, by joining casein molecules through covalent bonds.In this context, the objective of the present work is first to investigate the stability of cross-linked CMs under different pH, dissociating agents, temperature, and ethanol conditions. Then, verify their potential use as nanocarrier for entrapped cyanidine-3-O-glucoside (C3G), an anthocyanin present in several Brazilian’s fruits, that shows diverse bioactive properties in acid conditions. Two cross-linking agents were evaluated: genipin (GP) and transglutaminase (Tgase). We present a comparative study of the stability between native CMs and CMs cross-linked with GP or Tgase as a function of pH. Stabilities at different temperatures and ethanol concentrations were investigated in a pH range between 7.0 – 2.0 and results showed that the cross-linkingreaction stabilized CMs under the conditions tested.However, GP is not recognized as GRAS (safe for food applications) and further researches on toxicity would be required to implement their use as a food-grade cross-linker. For this reason, in the second part of our work, we focalize only on Tgase cross-linked CMswith perspectives of using it for food applications.Firstly we investigated on the possible interaction between casein molecules and C3G under acidic (pH 2.0) and neutral (pH 7.0) conditions. Then, the use of Tgasecross-linked CMs as nanocarrier for C3G at pH 2.0 and at pH 7.0 was explored. Binding constant as well as driving forces at different pH values were determined by thermodynamic analysis at different temperatures. At pH 2.0, hydrophobic association drive the interactions between caseins and C3G, whereas at pH 7.0, electrostatic interactions are the dominant binding forces. CMs Cross-linking by Tgase don’t affect the interactions between C3G and caseins meaning it can be used as efficient nanocarriers for anthocyanins such as C3G under acid conditions.